Effects of aminoreductone against the growth of food-borne bacteria in medium and in milk - Trang, Vu Thu (Vietnam Journal of Science and Technology, 2015)
The aim of this study was to determine the antimicrobial potential ofaminoreductone (AR), a product formed in the initial stages of the Maillardreaction, against common food-borne bacteria included food-spoilage andfood-pathogenic bacteria (Staphylococcus aureus, Bacillus subtilis, Enterococcusfaecalis, Listeria innocua, Listeria monocytogenes, Escherichia coli,Salmonella Typhimurium). AR showed strong inhibitory effects against allbacteria by disc susceptibility assay with inhibition zones ranged from 17 mm (B. subtilis) to 24.3 mm (S. aureus) indiameter. The minimum inhibitory concentrations (MIC) of AR ranged from 20 to26 mM. Among test strains, AR possessed bactericidal action to five isolates(S. aureus, B. subtilis, L. innocua, L. monocytogenes and S. Typhimurium) atthe concentration of less than 10 ´ MIC. AR also showedstrong inhibitory effect against food-borne bacteria even in milk (UHT milk andraw milk). These findings suggest that AR, a naturally formed antimicrobialagent present in thermally processed foods, has a promising potential for foodpreservation